Parametric optimization and kinetic modelling for organic matter removal from agro-waste derived paper packaging biorefinery wastewater - Jagaba, A.H. (Springer Science and Business Media Deutschland GmbH, 2022)
The state-of-the-art paper packaging biorefinery utilizes cellulose fibrous material from paddy straw and papaya latex to produce packaging products. This in turn generate wastewater with high organic matter content that if disposed without treatment will pollute water bodies and affect aquatic life below water. Therefore, to comply with âclean water and sanitationâ (SDG 6) and âlife below waterâ (SDG 14), this study assesses the efficacy of an extended aeration activated sludge (EAAS) in the treatment of paper packaging biorefinery wastewater (PPBW) by employing paddy straw-derived activated carbon as a biosorbent. Findings revealed that the system was able to achieve 95â98.2 and 90.62â94.96 biological oxygen demand (BOD5) and chemical oxygen demand (COD) reduction, respectively. The maximum organic matter removals were achieved at 2-day hydraulic retention time (HRT) and 60 PPBW concentration. To evaluate substrate removal rates, the first-order, modified StoverâKincannon and Grau second-order models were used. In the modified StoverâKincannon model, high correlation coefficients values R2 of 0.99986 and 0.99991 were obtained for COD and BOD5, respectively. Twenty grams COD/L/day and 50 gBOD5/L/day were obtained as Umsr for COD and BOD5, respectively, and 20.402Â g/L/day and 56.295Â g/L/day as KV constants for COD and BOD5, respectively. The COD and BOD5 biokinetic constant values for the Grau second-order organic matter removal rate constant kS were 36Â dayâ1 and 0.78Â dayâ1, respectively. Here, 0.9989 and 0.99928 were the obtained R2 values for COD and BOD5, respectively. The EAAS bioreactor system described by modified StoverâKincannon model was proven to best suit the experimental data. Therefore, the model can be used in designing an EAAS system and consequently predict the bioreactor behaviour. The result of this study provided a benchmark for the actual implementation of PSAC in PPBW treatment for COD and BOD5 removal. It has been proven that PSAC biosorbent sourced from a natural agro-waste material is essential and could be used as an efficient substance for organic matter removal. Operating expenses and associated savings were such that PASC was more attractive in an economic analysis of wastewater treatment demands. It is environmentally benign and offers a green treatment option to the PPBW. It could be an alternative to chemical materials because it is harmless to human health and proffer sustainable solution to potable water production. Â© 2022, The Author(s), under exclusive licence to Springer-Verlag GmbH Germany, part of Springer Nature.